Investigating the Effects of Peripheral Electrical Stimulation on Corticomuscular Functional Connectivity Stroke Survivors. Issue 3 (2nd April 2016) - Lai, Meei-I; Pan, Li-Ling; Tsai, Mei-Wun; Shih, Yi-Fen; Wei, Shun-Hwa; Chou, Li-Wei
Abstract : Background: Electrical stimulation (ES) in the periphery can induce brain plasticity and has been used clinically to promote motor recovery in patients with central nervous system lesion. Electroencephalogram (EEG) and electromyogram (EMG) are readily applicable in clinical settings and can detect real-time functional connectivity between motor cortex and muscles with EEG–EMG (corticomuscular) coherence. Objective: The purpose of this study was to determine whether EEG–EMG coherence can detect changes in corticomuscular control induced by peripheral ES. Methods: Fifteen healthy young adults and 15 stroke survivors received 40-min electrical stimulation session on median nerve. The stimulation (1-ms rectangular pulse, 100 Hz) was delivered with a 20-s on–20-s off cycle, and the intensity was set at the subjects' highest tolerable level without muscle contraction or pain. Both before and after the stimulation session, subjects performed a 20-s steady-hold thumb flexion at 50% maximal voluntary contraction (MVC) while EEG and EMG were collected. Results: Our results demonstrated that after ES, EEG–EMG coherence in gamma band increased significantly for 22.1 and 48.6% in healthy adults and stroke survivors, respectively. In addition, after ES, force steadiness was also improved in both groups, as indicated by the decrease in force fluctuation during steady-hold contraction (−1.7% MVC and −3.9%MVC for healthy and stroke individuals, respectively). Conclusions: Our results demonstrated that EEG–EMG coherence can detect ES-induced changes in the neuromuscular system. Also, because gamma coherence is linked to afferent inputs encoding, improvement in motor performance is likely related to ES-elicited strong sensory input and enhanced sensorimotor integration.